Una propuesta de Creditmetrics y Expected Shortfall para medición de riesgo crediticio (2010)
This paper presents a simple method to quantify credit risk. The idea is to combine the CreditMetrics methodology with the Expected Shortfall risk measure. We apply this method for a stand-alone bond and a portfoMetrics is based on VAR rik measure. We apply this method for a stand-alone bond and a portfolio of two bonds. Due to the fact that CreditMetrics is based on VAR risk measure and this measure is no coherent, it is proposed the use of a coherent risk measure. Expected Shortfall solves the problem of non-subadditivity property of VAR but by definition Expected Shortfall is in general greater than VAR.